Distribution of major, minor and trace elements in Antarctic offshore and coastal seawters: correlation among sites and variables by pattern recognition - ABOLLINO, Ornella; BUOSO, Sandro; LA GIOIA, Carmela; SARZANINI, Corrado; MENTASTI, Edoardo; M. Aceto (International Journal of Environmental Analytical Chemistry, 2004)
The composition of seawater in the Ross Sea (Antarctica) was investigated. The distribution of heavy metals (Cd, Cu, Fe, Mn, Ni), minor and trace (B, Ba, Li, Sr, Si) and major (Na, K, Ca, Mg) elements in coastal and offshore sites was determined. The samples were collected during the XIII Campaign of the Italian ‘‘National Programme of Research in Antarctica’’, PNRA, at different depths and different stages of the Antarctic summer. In the subsequent campaign the concentrations in the water top micro-layer, and just below it, were compared. Results are also given for the data treatment by pattern recognition.